2021
DOI: 10.32609/0042-8736-2021-6-139-156
|View full text |Cite
|
Sign up to set email alerts
|

Innovative profile of the Russian pharmaceutical industry

Abstract: InnoThe article examines the specifics of innovative activity of Russian drug manufacturers, which in the context of a COVID-19 pandemic become a matter of national security. The research is based on panel data: out of a total of 1,816 enterprises in the industry, a sample of 345 innovatively active enterprises is formed with a time series of data 20 years long. The sample is diversified by the scale of enterprise activity into 4 groups: micro enterprises, small, medium, and large enterprises. These types of e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…This, ultimately, gives such enterprises the opportunity to reveal their innovative potential at the stage of deep maturity. This conclusion correlates with the results of the empirical studies (Morck and Yeung, 2001;Podshivalova et al, 2021), the authors of which concluded that small firms realize their innovative potential only at the stage of maturity, when they have accumulated the appropriate capital. In addition, the obtained results helped us identify a new reason for the low innovation activity of small industrial enterprises-the insufficient number of mature manufacturing companies.…”
Section: The Long-lived Sample Groupsupporting
confidence: 86%
“…This, ultimately, gives such enterprises the opportunity to reveal their innovative potential at the stage of deep maturity. This conclusion correlates with the results of the empirical studies (Morck and Yeung, 2001;Podshivalova et al, 2021), the authors of which concluded that small firms realize their innovative potential only at the stage of maturity, when they have accumulated the appropriate capital. In addition, the obtained results helped us identify a new reason for the low innovation activity of small industrial enterprises-the insufficient number of mature manufacturing companies.…”
Section: The Long-lived Sample Groupsupporting
confidence: 86%